The prevalence of statin intolerance worldwide: a systematic review and meta-analysis with 4, 143, 517 patients. (14th October 2021) - Bytyci, I; Bajraktari, G; Sahebkar, A; Penson, P E; Rysz, R; Banach, M Y
Abstract: Background: The efficacy of statins in the prevention and treatment of cardiovascular disease is well established. Despite their large benefit, statin intolerance (SI) is still an important clinical challenge. In this meta-analysis, we aimed to estimate the overall prevalence of SI, the prevalence based on different diagnostic criteria and different disease settings. Methods: We searched all electronic databases until the end of March 2021 for studies that reported the prevalence of SI. The primary endpoint was overall prevalence and prevalence based on different diagnostic criteria (National Lipid Association/NLA, International Lipid Expert Panel/ILEP and European Atherosclerosis Society/EAS). The secondary endpoint was the SI prevalence in the groups of patients with different diseases' settings. A random-effects model was applied to estimate the overall pooled prevalence. Results: One hundred and seventy-six studies (112 RCTs; 64 cohort studies) with 4, 143, 517 patients were included in the analysis. The overall SI prevalence was 9.1% (8.1 to 10%). The prevalence based on NLA criteria was similar compared to ILEP and EAS (7.0, 6.7, 5.9%, respectively; p>0.05). The prevalence of SI in RCTs studies was significantly lower in comparison to the cohort studies (4.9 vs. 17%; p<0.001). The SI prevalence in patients both in primary and secondary prevention was much higher (18%; mainly due to dominant cohort studies) than in the separate analysis of those in primary and secondary prevention (8.2, 9.1%, respectively; p<0.05). In the subgroup analysis based on different disease in the primary prevention: familial hypercholesterolemia, hypercholesterolemia, dyslipidemia and diabetes mellites, the prevalence was 9, 12, 13 and 6%, respectively) and in the secondary prevention: stable coronary artery disease, acute coronary syndrome and myocardial infarction – 8, 13, and 13%; respectively (Figure 1). Conclusions: Based on the data from analysis of over 4 million patients, the overall SI prevalence is low, and even lower based on the recognized international definitions. These results support the concept that complete intolerance might be often overestimated and highlight the need for very careful examination of patients with statin intolerance. FUNDunding Acknowledgement: Type of funding sources: None.